Metody taksonomiczne w badaniach środowiska naturalnego - Sej-Kolasa, Małgorzata (Taxonomic methods for natural environment research, 2005)
An indispensable tool for managing the environment is the possibly most detailed and most accessible information. Society-economy-environment system is described by many diagnostic features. The objective of this article is to emphasise the particular usefulness of the taxonomic methods for environmental research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 220-226